Empowering Digital Parenting through Web-Based Admission System and Technology Literacy Training for Families in Early Childhood Education - Kalifia, Anna Dina; Astrianty, Ledy Elsera; Sanjaya, Fadil Indra; Pramudwiatmoko, Arif (MEKONGGA: Jurnal Pengabdian Masyarakat, 2025)
This community service program was conducted to address two main problems identified at TK Pamardisiswi Muja Muju, Yogyakarta: the limited digital literacy among parents in guiding their children’s use of technology, and the absence of an accessible web-based student registration system. The program was implemented through an educational and technological approach, including observation, interviews, system development, training, and evaluation. The developed information system simplified the administrative process and expanded access to educational information. The training provided not only improved participants’ technical skills in operating the system but also enhanced their understanding of digital parenting. Evaluation results indicated a significant increase in participants’ abilities: login (35% to 92%), online form completion (28% to 89%), document upload (25% to 86%), understanding of digital content risks (19% to 81%), and awareness of parental roles in guiding children in the digital environment (30% to 90%). This program contributed to strengthening family digital literacy and advancing educational digitalization in early childhood settings.